Radicalism - McLaughlin, P. author. aut Link
VI, 214 p.
Keywords: Confusion, controversy and even fear surrounds the political phenomenon of radicalism. This book attempts to make conceptual and historical sense of this phenomenon, both as a kind of practice and as a kind of thought, before defending it in a traditional if unfashionable form: a form that is historically progressive and politically humanistic.